COMPETITIVE EDUCATION AS A SIGNIFICANT FACTOR OF A NATIONAL ECONOMIC GROWTH - Zenčaka, Andra; Šenfelde, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In order to ensure sustainable economic growth in the country, a knowledge-based economy must be implemented in the country, in which one of the essential factors is educated human resources, globally competitive and able to quickly respond to changes in the structure of the national economy. Researches carried out in the world suggests that technological developments will require a fifth of the workers to change their job in the coming decades. In this case, acquisition of knowledge, skills and competences will not necessarily require a long-term training process, but on the contrary it will have to be fast and of high-quality in order to respond to changes in the labor market. With the growth of global competition, with the increase in interaction between education and sustainable national growth, it is necessary to ensure the functioning of a competitive education system. As education and its quality are one of the most important conditions for solving global problems in today`s world, the aim of the research is to analyze the features of competitive education, to demonstrate its impact on the growth of national economy branches and to demonstrate how their effective interaction can ensure the country`s sustainable economic growth. The research analyzes the main indicators characterizing the education system in Latvia – the number of education institutions, the number of teachers in the educational institutions, their quality, the number of students and the financing from the state budget for education in the period from 2014 to 2016. Certain features of competitive education and their impact on sustainable economic growth of the country, the main results of the implementation of competitive education are summarized and the possible relationship between competitive education and the country`s economic growth is reflected. In the research, the following methods, generally recognized in the economy, have been used: document analysis, comparison, classification, and statistical analysis methods. As a result of the research, the authors will determine the factors influencing the competitiveness of education, as well as develop recommendations to be introduced in order to implement competitive education in Latvia in line with the development trends of the national economy sectors, to prepare knowledgeable and globally competitive human resources that would promote the long-term national economic growth.